Um protótipo de autoria de histórias OCC-RDD para ambientes de aprendizagem presencial - Buttignon, Karina (2015)
This study was designed with the desire to propose new approaches to teaching and learning process, modeling a teaching methodology that could support the teacher and the student, leading them to a more interactive experimentation for teaching in the course of computing by means of narratives as a way to teach using the OCC-RDD technique widely discussed in GEMS (Study Group on Software Modeling) of the TIDD at PUC / SP, supported by cognitive levels of Bloom's Taxonomy. The research proposes the development of a prototype for creating and manipulating stories within the educational context dealing conjectured scenarios scenes "objective," "mishap" and "Catastrophe", provided for in the OCC-RDD technique already mentioned. The literature review still permeates the work of Mieke Bal on the dynamics of functioning of fables, including guiding the entries used in this study. The motivation for this study, in addition to everyday observation arising from the unrest in the teaching practice, took breath in contact with the dropout data recorded in the area of computing, especially in the learning point of view. Among the situations mentioned by bibliographic studies, no understandings of the disciplines that require proficiency in logic, are the most incidents. Having done this formation process guided by the tenets found in the literature review, we understand the importance of bringing the creation of a prototype that could give plasticity ace mental conceptions formatted in the process of understanding of all these variables. The dissertation this separated into six chapters the first corresponds to contextualize the work, the second chapter deals with the theoretical framework of the relationship of computing with cognitive science, the OCC-RDD technique and its characteristics, the third chapter is based on the theories of Mieke Bal to construct fables in an attempt to create OCC-RDD fables scenarios in the fourth chapter presents three case studies applied at a college in the course of computing, chapter five describes and presents the model of a prototype and sixth chapter completion and collaborations for future work